Effectiveness of person-centered intervention on obstetric violence during facility-based childbirth among women who delivered in public hospitals in Southwest Ethiopia - Taye, Ayanos; Belachew, Tefera (Frontiers in Public Health, 2025)
BackgroundObstetric violence (OV) is a significant public health issue affecting reproductive health services and maternal health outcomes. Despite studies documenting its prevalence in Ethiopia, no experimental studies have assessed intervention effects. This study evaluates person-centered interventions for OV in public hospitals in Southwest Ethiopia, using an experimental design.MethodsA quasi-experimental study was conducted in Southwest Ethiopia involving 396 women, divided into a control group (CG; n = 198) and an intervention group (IG; n = 198). The intervention group received person-centered interventions, including respectful maternity care workshops and maternal recognition certificates, while the control group received standard care. Statistical analyses included t-tests and regression to assess the intervention’s impact on OV.ResultsThe proportion of women who utilized companions during facility-based childbirth was higher in the intervention group [25.8%; 95% confidence interval (CI): 19.6, 31.9%] than in the control group (12.1%; 95% CI: 7.5, 16.7%). The proportion of women who experienced OV decreased significantly in the intervention group compared with the control group (IG: 42.05 ± 6.97; CG: 66.45 ± 12.12; p < 0.000), with a 26.00-point decrease in the experimental group. The multivariable general linear model revealed that the mean difference (MD) of non-confidential care (MD = −3.28; 95% CI: −3.66, −2.90), undignified care (MD = −7.03; 95% CI: −7.76, −6.31), non-consented care (MD = −5.64; 95% CI: −6.35, −4.92), physical abuse (MD = −4.80; 95% CI: −5.30, −4.31), discrimination (MD = −3.37; 95% CI: −3.79, −2.94), and detention (MD = −0.28; 95% CI: −0.51, −0.05) were significantly reduced in the intervention group, with effect sizes of 0.421, 0.480, 0.380, 0.479, 0.382, and 0.014, respectively. Women in the intervention group had an OV score that was, on average, 23 points lower (β = −23.42; 95% CI: −25.40, −21.44) than those in the control group. Additionally, women in the intervention group who had frequent contact with healthcare providers experienced, on average, a seven-point lower OV score (β = −7.47; 95% CI: −4.055, 18.37) than those in the control group.ConclusionThis study revealed that implementing person-centered interventions through respectful maternity care workshops, maternity open days, and maternal certificates of recognition significantly decreases the incidence of OV and ultimately promotes respectful maternal care, improving maternal healthcare services.